Innate factors and ontogeny determine nonbreeding areas of migrant songbirds - K.P. Lamers; J. Ouwehand; R. Ubels; M. Nicolaus; C. Camacho; J. Potti; F. Bell; M. Burgess; H.M. Lampe; J.Å. Nilsson; A. Kerimov; T. Ilyina; et al. (Science, 2026)
Migratory birds connect ecosystems worldwide and often show connectivity between breeding and nonbreeding areas, meaning that individuals have nonbreeding (“wintering”) locations close to others from the same breeding population. Although much work has characterized migration routes, we know little about what determines nonbreeding areas. We tracked pied flycatchers ( Ficedula hypoleuca ) from their entire breeding range and identified population-specific nonbreeding areas. Using an egg translocation experiment between the Netherlands and Sweden, we show that both inheritance and natal environment determine nonbreeding areas. Genetically Dutch birds that hatched in Sweden had nonbreeding areas intermediate between Swedish and Dutch populations. Although an inherited basis for migratory routes and nonbreeding areas may hamper rapid adaptation to a changing world, dispersing individuals can create new breeding–nonbreeding site combinations.